Detailed composition evolution of food waste in an intermittent self-agitation anaerobic digestion baffled reactor. (January 2021) - Qi, Wei-Kang; Liu, Li-Fang; Shi, Qi; Wang, Cong; Li, Yu-You; Peng, Yongzhen
Graphical abstract: Highlights: The evolution of an innovative reactor used to process food waste was studied. The treatment of various soluble and solid components was analyzed. The removal principles of carbohydrate, protein, and lipids is discussed. Volumetric loading reached 2.43 L-Gas/L-Re, mainly produced in half of the reactor. Abstract: This study used an intermittent self-agitation anaerobic baffled reactor (SA-ABR) to treat food waste. The organic matter and detailed composition evolution were analyzed under continuous operation. The gas production rate was 2.43 ± 0.18 L-Gas/d/L-Re, and the biogas conversion was 0.94 L-Gas/g-TS. The effluent concentration of total chemical oxygen demand (COD) was 22.5 ± 2.44 g/L, and the removal rate of soluble COD was always over 97%. In this study, the removal rates of carbohydrate, protein, and lipids in the SA-ABR treatment were 95%, 60%, and 85%, respectively, and the concentrations were 0.11 g/L, 0.32 g/L, and 0.33 g/L, respectively. The conversion of soluble organic matter was much higher than that of insoluble substrates. The concentration of soluble pollutants was significantly lower than that of pollutants in suspended matter. The treatment of organic matter in the first half of the SA-ABR was 85–100% that of the entire reactor.